2009
DOI: 10.1097/wnp.0b013e3181af209c
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Sleep Spindles and Activities of the Cerebral Cortex After Hemispheric Stroke As Determined by Simultaneous EEG and MEG Recordings

Abstract: This study aimed to determine the relationships between the amplitude and cortical-activating areas in each hemisphere for 14-Hz centro-parietal spindles to clarify the involvement of the cortex in the asymmetry of spindles after hemispheric stroke with putaminal or thalamic hemorrhage using simultaneous recording of the electroencephalogram and magnetoencephalogram. Spontaneous cortical activities during sleep stage 2 (spindles) were simultaneously recorded from 10 patients with putaminal or thalamic hemorrha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Gottselig et al [31] (2002) found an association between the power and coherence of sleep spindle frequency activity and long-term stroke outcome. Urakami [32] (2009) showed that reduced spindles were associated with an absence of activation in the ipsilateral hemisphere.…”
Section: Sleep and Acute Strokementioning
confidence: 99%
“…Gottselig et al [31] (2002) found an association between the power and coherence of sleep spindle frequency activity and long-term stroke outcome. Urakami [32] (2009) showed that reduced spindles were associated with an absence of activation in the ipsilateral hemisphere.…”
Section: Sleep and Acute Strokementioning
confidence: 99%
“…Sleep, through neuroplastic and encoding processing mediated mainly by slow waves sleep (SWS) and sleep spindles, plays an active role in this recovery process. Indeed, the finding that sleep spindles of stroke patients have a reduced amplitude as well as a reduced cortical activation than healthy subjects ( 73 , 74 ) and that SWS remains lower over the perilesional area ( 75 ) supports the fundamental role of sleep in recovery.…”
Section: Meg Studies On Brain Reorganization and Rehabilitation Aftermentioning
confidence: 87%
“…Application of inversion techniques in patient populations should be encouraged, as in investigating the cortex involvement in the asymmetry of spindles after hemispheric stroke (Urakami, 2009 ) and the generation of spindles in temporal lobe epilepsy (Del Felice et al, 2013 ). A topic that has not yet been addressed concerns the extraction of parameters related to the phenomenology of intracranial current sources.…”
Section: Estimation Of Intracranial Current Sources For Sleep Spindlementioning
confidence: 99%